2013
DOI: 10.1016/j.scriptamat.2013.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal stability in nanostructured bainitic steel

Abstract: We report an attempt at increasing the thermal stability of nanocrystalline bainite to tempering heat-treatments, by enhancing the silicon concentration of the alloy. Validation experiments have been conducted using synchrotron X-radiation during tempering heat treatment. It is found that the change in alloying successfully stabilises the austenite at elevated temperatures by retarding cementite formation to temperatures as high as 500 • C. Other changes reflected in the lattice parameters of the major phases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…[12,13] Development of alloys with increased temperature stability is in progress; this will rely on further suppressing carbide precipitation to increase the stability of the nanostructure. [14] So there are a several strong motivations to characterize the tempering behavior of these nanostructured steels.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Development of alloys with increased temperature stability is in progress; this will rely on further suppressing carbide precipitation to increase the stability of the nanostructure. [14] So there are a several strong motivations to characterize the tempering behavior of these nanostructured steels.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous work [22] has shown that the addition of large amount of cementite-insoluble elements can delay the thermal decomposition, it is unlikely that such an approach can sufficiently suppress cementite precipitation: ultimately, a mixture of ferrite and cementite is required by equilibrium. A novel approach was therefore considered: to minimize the carbon content of retained austenite and thereby reduce the driving force for the precipitation of carbides.…”
Section: B Alloymentioning
confidence: 99%
“…Two approaches were considered to develop novel alloys: an extension of previous work [22] to introduce as many atoms that are insoluble in cementite as possible and a new concept to minimize the carbon content while still obtaining the desired microstructure.…”
Section: Alloy Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work on nanostructured bainite has shown that the decomposition occurs during isothermal heat treatment at temperatures of 400 • C or above [27,29,38,39]. However, these experiments involve continuous heating, so dilatometric experiments were done to measure the temperature range over which the substantive decomposition of austenite occurs.…”
Section: (F) Decomposition Of Retained Austenitementioning
confidence: 99%